Analisis Pengaruh Opinion Shopping, Leverage, dan Kepemilikan Institusional Terhadap Opini Audit Going Concern: (Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar Pada Jakarta Islamic Index Tahun 2019-2022) - Septia Anggraini; Dewi SPA; Djoko Kristianto (Universitas 45 Surabaya, 2024)
This research aims to analyze the influence of opinion shopping on going concern audit opinions in manufacturing companies listed on the Jakarta Islamic Index in 2019-2022, analyze the influence of leverage on going concern audit opinions of manufacturing companies listed on the Jakarta Islamic Index in 2019-2022, and analyze The influence of institutional ownership on going concern audit opinions of manufacturing companies listed on the Jakarta Islamic Index for 2019-2022. This research is a case study of manufacturing companies listed on the Jakarta Islamic Index for 2019-2022. This research used a sample of 132 with a sampling technique using purposive sampling. Data collection techniques use library research. The data analysis technique uses multiple linear regression analysis methods, t test, f test, and determination test. The research results show multiple linear regression analysis Y= 6.332 + 0.477 X1 + 0.348 X2 + 0.541 Leverage has a significant effect on the Manufacturing Going Concern Audit Opinion on the 2019-2022 Jakarta Islamic Index. Institutional ownership has a significant influence on the Manufacturing Going Concern Audit Opinion on the 2019-2022 Jakarta Islamic Indeks.